Interactions between shape-persistent macromolecules as probed by AFM - Blass, Johanna; Brunke, Jessica; Emmerich, Franziska; Przybylski, Cédric; Garamus, Vasil M.; Feoktystov, Artem; Bennewitz, Roland; Wenz, Gerhard; Albrecht, Marcel (Beilstein Journal of Organic Chemistry, 2017)
Water-soluble shape-persistent cyclodextrin (CD) polymers with amino-functionalized end groups were prepared starting from diacetylene-modified cyclodextrin monomers by a combined Glaser coupling/click chemistry approach. Structural perfection of the neutral CD polymers and inclusion complex formation with ditopic and monotopic guest molecules were proven by MALDI–TOF and UV–vis measurements. Small-angle neutron and X-ray (SANS/SAXS) scattering experiments confirm the stiffness of the polymer chains with an apparent contour length of about 130 Å. Surface modification of planar silicon wafers as well as AFM tips was realized by covalent bound formation between the terminal amino groups of the CD polymer and a reactive isothiocyanate–silane monolayer. Atomic force measurements of CD polymer decorated surfaces show enhanced supramolecular interaction energies which can be attributed to multiple inclusion complexes based on the rigidity of the polymer backbone and the regular configuration of the CD moieties. Depending on the geometrical configuration of attachment anisotropic adhesion characteristics of the polymer system can be distinguished between a peeling and a shearing mechanism.
Keywords: AFM; cyclodextrin; inclusion complexes; molecular recognition; polyconjugated polymers; shape persistent polymers